ELABORATION OF STRATEGIC POLICIES FOR ENSURING THE ANGOLAN ECONOMY’S COMPETITIVENESS - B. Sebastiao (Publishing House of the State University of Management, 2017)
The article focuses on the origin of the economic concept «competitiveness» and brings a definition of this term. In addition, considering the theoretical bases of competitiveness at the macro level, the author reviews the concept «competitiveness of a country» and identifies the key problems, which put obstacles in the way of ensuring the Angolan economy’s competitiveness and suggests strategic policies for solution of these problems.